Law as Geopolitical Instrument - Lawrence Brenner (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2026)
This paper investigates the relationship between foreign direct investment (FDI) and its impact on the strategic autonomy of the Philippines. The research advocates for FDI to be considered holistically rather than only as economic discourse. The legal mechanisms utilised in the FDI process act as a key consideration when considering the geopolitical influence of FDI. The research uses a New Legal Realist approach to analyse EU regulatory conditionalities in comparison to Chinese contractual structures to investigate the impact of these upon Philippines strategic autonomy without impacting sovereignty. The research utilises primarily legal instruments, policy documentation and case studies such as the EU Global Gateway and Chinese led mining projects in the Philippines to show that both foreign investment approaches from the EU and China limit domestic policy formation in the Philippines. The EU investment primarily shapes governance through gradual regulatory alignment and ESG conditionalities, whilst the Chinese approach constrains the Philippine party contractually, creating operational dependence. The research finds that strategic autonomy is not eroded by a direct loss of sovereignty, but rather through legal and institutional limitations which reconfigure domestic decision making. The research shows that FDI is an infrastructural form of geopolitical power, projected through law, rather than relying solely upon market exchange.